Psicanálise e educação : respostas encontradas pelos professores diante das manifestações de sexualidade das crianças na escola - Luiza Pinheiro Mendes Ferreira (2016)
This study aims to discuss the contribution of psychoanalysis possibilities for education, especially in cases where there is distress on the part of teachers related to the manifestations of sexuality of children in preschools. The chosen research methodology was the psychoanalytic conversation and the theoretical route was designed from the speeches of the participating teachers. Thus, we covered the main texts of Freud that address child sexuality - and the traumatic nature that it can represent both for the child and for the adult - as well as for publications that address the possibilities of relationship between psychoanalysis and education. It is proposed along this dissertation that look at this issue is shifted from the malaise of teachers and head to the solutions for them to deal with sexuality impasses. Finally, it is suggested that psychoanalysis has its insertion in school through the Conversations device as a way to appease the anguish teachers and enable the development of new responses in distress.